2021
DOI: 10.1021/acs.chemmater.1c00071
|View full text |Cite
|
Sign up to set email alerts
|

Search and Structural Featurization of Magnetically Frustrated Kagome Lattices

Abstract: We have searched ∼40 000 fully ordered, main-group containing solids in the Inorganic Crystal Structural Database and ∼13 000 structures of the American Mineralogist Crystal Structure Database to identify compounds containing a transition metal or a rare-earth kagome sublattice, a geometrically magnetically frustrated lattice, ultimately identifying ∼500 materials. A broad analysis of the chemical and structural trends of these materials shows three types of kagome sheet stacking and several classes of magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
(70 reference statements)
0
17
0
Order By: Relevance
“…In some of these compounds, for example, transition-metal oxides with a kagome lattice built by a n d element, orbitals that are not used for bonding with a main group element can be low in energy and partially filled. However, these orbitals do not go on to form kagome bands but localize the n d electrons on the lattice sites instead . This can be understood as a consequence of higher oxidation states that the transition metal atoms have in these compounds, which reduces their willingness to delocalize the remaining electrons through kagome in-plane bonding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some of these compounds, for example, transition-metal oxides with a kagome lattice built by a n d element, orbitals that are not used for bonding with a main group element can be low in energy and partially filled. However, these orbitals do not go on to form kagome bands but localize the n d electrons on the lattice sites instead . This can be understood as a consequence of higher oxidation states that the transition metal atoms have in these compounds, which reduces their willingness to delocalize the remaining electrons through kagome in-plane bonding.…”
Section: Resultsmentioning
confidence: 99%
“…However, not all compounds with a kagome net will have properties dictated by it. Previously, a search of kagome compounds was performed to find compounds exhibiting frustrated magnetism which arises from electron localization on kagome sites . The main goal of this work is to derive rules that predict if bands arising from the kagome lattice (Figure ) will exist at the Fermi level and dominate the low-energy behavior of a kagome compound.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic topology of the cobalt-shandite was estimated as a guide to the realization of strong AHE in magnetic and topological semimetals. Researchers started to exploit further properties of Sn 2 Co 3 S 2 =Co 3 Sn 2 S 2 including zero field Nernst effect, thermoelectric and magnetocaloric properties, as well as critical and Skyrmion behavior (see e. g. [28][29][30][31][32][33][34][35] ).…”
Section: Introductionmentioning
confidence: 99%
“…Materials containing the kagomé lattice, consisting of a two-dimensional network of cornersharing triangles, have long been studied for the novel phenomena they are often host to, including strongly correlated topological states, 1 superconductivity, 2 and most notably high degrees of magnetic frustration. [3][4][5] One such family of materials, the jarosites, (AB 3 (XO 4 ) 2 (OH) 6 , where A = a monovalent or divalent cation, B = a trivalent cation, and XO 4 = a divalent polyanion group) have long been studied for the impact of kagomé-sublattice vacancies on their magnetic properties. 6,7 The majority of the jarosite phases possess metal-ligand-metal (M-L-M) bridging angles on the order of 130-140°, are known to order antiferromagnetically between T = 55-65 K, and are considered near-ideal Heisenberg antiferromagnets, with weakly ferromagnetic intralayer coupling and antiferromagnetic interplanar coupling.…”
Section: Introductionmentioning
confidence: 99%
“…13 A recent computational study suggested that corkite, PbFe 3 (PO 4 )(SO 4 )(OH) 6 , a related mineral with a similar calculated ground state Ising spin configuration to the jarosites, would benefit from magnetic characterization to determine whether it behaves as a Heisenberg antiferromagnet, or if it exhibits more interesting magnetism at low temperatures. 5 The structure of corkite has been previously probed in both natural and synthetic samples (Figure 1a, 1b), however its magnetic properties have not yet been reported. 14,15 While pure phase specimens of corkite would not contain the rather reactive H 3 O + species, it is not known whether the substitution of one sulfate group per formula unit with a higher-valent, larger phosphate group could disrupt the interlayer couplings observed in the pure jarosites, producing a more ideal Heisenberg antiferromagnet.…”
Section: Introductionmentioning
confidence: 99%